SIMULASI ALIRAN FLUIDA PADA INSTALASI GASIFIKASI TIPE DOWNDRAFT: Fluid Flow Simulation in Downdraft Type Gasification Installation - Wijianto, Agus; Alfitrah, Fajar (Universitas Negeri Jakarta, 2024)
The development of energy is very important to maintain oil reserves and also substitute for fossil fuels. Agricultural waste can be used as an alternative raw material to assist in the depletion of petroleum reserves and increase the use value of agricultural waste. Gasification is a process that converts energy into syngas that can be used for fuel. Fluid flow simulation research in the downdraft was conducted to determine the effect of the heat distribution or temperature on the gasification equipment installation and the effect of the cooling water mass flow rate on the airflow out of the reactor. Numerical study method using computational fluid dynamic solidworks flow simulation software. The fixed variables in the simulation are inlet air velocity 1.27, 1.36, and 1.49 m/s where this figure is obtained from an experiment to test the characterization of the downdraft actual the simulation in the reactor shows the temperature of the combustion reactor is 800-850ºC to be 400-450ºC at the reactor output. The simulation on the heat exchanger is carried out to reduce the air temperature to the temperature operating engine. The heat exchanger uses water fluid with a mass flow rate of 0.05 kg/s. The best simulation is obtained at the variation of air velocity 1.27 m/s and temperature reactor 900ºC where the output temperature is 92.11ºC. Doing a new experiment on gasification, then doing a simulation first, will make the gasification work easier.